2020
DOI: 10.1093/jhered/esaa058
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Asex: A Clonal Lexicon

Abstract: Organisms across the tree of life have complex life cycles that include both sexual and asexual reproduction or that are obligately asexual. These organisms include ecologically dominant species that structure many terrestrial and marine ecosystems, as well as many pathogens, pests, and invasive species. We must consider both the evolution and maintenance of these various reproductive modes and how these modes shape the genetic diversity, adaptive evolution, and ability to persist of the species that exhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…The Spring 2019 National College Health Assessment reported more than one-third of college students stated that their finances had been traumatic or very difficult to handle during the past 12 months [ 6 ]. Unfortunately, the COVID-19 pandemic further worsened the financial situation for many students in higher education [ 7 , 8 ]. The National College Student COVID-19 Survey revealed that 30% of students reported losing a job needed to help pay for college, 77% of students reported that the pandemic reduced their ability to earn income to support their education, and 64% stated that their need for financial aid increased due to the pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Spring 2019 National College Health Assessment reported more than one-third of college students stated that their finances had been traumatic or very difficult to handle during the past 12 months [ 6 ]. Unfortunately, the COVID-19 pandemic further worsened the financial situation for many students in higher education [ 7 , 8 ]. The National College Student COVID-19 Survey revealed that 30% of students reported losing a job needed to help pay for college, 77% of students reported that the pandemic reduced their ability to earn income to support their education, and 64% stated that their need for financial aid increased due to the pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on species with agametic formation of asexual offspring, often termed clonal reproduction, that has single or multiple cells of somatic tissue as precursors [15]. These species proliferate by producing new modules through diverse mechanisms such as budding, branching or fission (Figure 1), creating a population of ramets (a module existing as an independent physiological entity) belonging to a genet that dates back to a single zygote.…”
Section: Somatic Mutations and Within-individual Genetic Heterogeneitymentioning
confidence: 99%
“…Clonal reproduction refers to the formation of new individuals that are genetically nearly identical to the parent via mitosis in the absence of genetic recombination (De Meeûs et al, 2007). This reproductive mode is widespread in multicellular organisms, and has many different forms, such as vegetative multiplication (animals and plants), parthenogenesis (animals), apomixis (plants), and gynogeneis or pseudogamy (De Meeûs et al, 2007; Orive & Krueger-Hadfield, 2021). In multicellular clonal species, a module or ramet (Harper & White, 1974) is the basic modular unit with an ability to live independently, while a genet (synonymous with clone) is the product of a single zygote from gamete fusion (Noble et al, 1979), and comprises all ramets that emerge via mitosis (i.e., clonemates) during its lifetime.…”
Section: Introductionmentioning
confidence: 99%